The Relationship of Plant Types Familia Araceae on The Mountain Sidole Track Central Sulawesi Based on Morphological Character - Samsurizal M. Suleman; I Made Budiarsa; Achmad Ramadhan; Moh. Iqbal; I Komang Suletra (Jurnal Biologi Tropis, 2022)
The Araceae family plant in the Mount Sidole has a diversity and variety of life forms. The purpose of this study is to describe the family relationship of Araceae family based on morphological characters. Sampling using the path method (belt transect) with free collection techniques. The size of the track used is 10 m wide and ± 15 km long along the Sidole Mountain climbing track at an altitude of 400-1780 m above sea level. Morphological data measurement refers to 37 meristic and qualitative characters. Processing data using the File Editor Program (PFE) and analyzed with the Multivariate Statistical Package (MVSP) program. Determination of similarity index with the Simple Matching Coefficient method and kinship between types using the Unweighted Pair-Group Method Using Arithmetic Average (UPGMA). The results of specimen collection are 26 species. Based on the dendrogram of Familia Araceae divided into three groups. Group I are 9 species of hemiepipitic groups which cluster at a coefficient of 76%, namely Amydrium medium, Pothos scandens, Epipendrum sp., Scindapsus treubii, S. pictus, Rhaphidophora sp., R. sylvestris, R. lobbii and R. puberula. Group II are 8 species of geophytes grouping at 77% coefficient, namely Colocasia oresbia, C. esculenta, Xanthosoma violaceumm, X. sagittifolium, Apoballis mutata, Alocasia sp., A. longiloba and A. Macrorrhizos. Group III are 9 species of geophytes grouping at 82% coefficient, namely Spathiphyllum commutatum, Schismatoglottis inculta, S. lancifolia, S. wallichii, S. asperata, S. cadieri, S. calyptrata and S. calyptrata ssp flagelliforme and Aglaonema nitidum.